La banqueta insegura en una colonia en vía de gentrificación: la construcción de los otros desde las relaciones vecinales - Aguilar Díaz, Miguel Ángel; Capron, Guénola (El Colegio de México A.C., 2022)
The analysis of the use and meaning of the sidewalks allows the understanding of social relations among neighbors and their formal and informal management. In the well-being of a local environment, the quality, walkability and use of the sidewalks are an important issue. Here is presented a research experience about the social life around the sidewalks in a middle class central neighborhood in Mexico City that is undergoing a gentrification process. Also are analyzed the conflicts that arise among neighbors, the atmosphere of insecurity and different strategies to cope with it.